2011
DOI: 10.1080/09593330.2010.497500
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic ammonium removal from reject water: partial nitrification and anammox in one‐reactor versus two‐reactor systems

Abstract: Removal of total nitrogen from anaerobically digested sludge reject water by a fully autotrophic process in either one- or two-reactor systems was compared. Autotrophic nitrogen removal is currently most often applied in the one-reactor system primarily in the DEMON configuration. The two-reactor systems had a similar nitrogen removal rate to the one-reactor systems. It was evident that the limiting step was partial nitrification. Increase in partial nitrification can be difficult in a one-reactor system, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…As stated in several studies, the actual bottleneck in the overall capacity of N-removal advanced treatment systems is the limiting capacity of the PN compared to anammox capacity [6,8,28]. Consequently, the novel technology presented in this study can be useful to improve the capacity of N-removal via nitrite.…”
Section: Microbial and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in several studies, the actual bottleneck in the overall capacity of N-removal advanced treatment systems is the limiting capacity of the PN compared to anammox capacity [6,8,28]. Consequently, the novel technology presented in this study can be useful to improve the capacity of N-removal via nitrite.…”
Section: Microbial and Chemical Analysismentioning
confidence: 99%
“…Consequently, the development of robust technologies for PN at higher nitrogen loading rates (NLR) is required to improve the capacity of the autotrophic N-removal [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lower the SRT, the higher are the specific nitrifying rates [18][19][20]. However, the activated sludge systems working at low SRT have a limited treatment capacity due to the low biomass concentration that can be achieved and it was reported that the SHARON process could be limited by this restriction [21]. The way to increase the biomass concentration and, consequently, the treatment capacity is working with biomass retention, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, an effective treatment process for nitrogen removal is desired. The anaerobic ammonia oxidation (Anammox) process, which involves simultaneous conversion of ammonium and nitrite into nitrogen gas under an anaerobic condition, has recently been attracting attention [4][5][6]. This is because it consumes less energy, produces less sludge and requires fewer carbon sources for denitrification as compared to the conventional nitrification and denitrification process [7].…”
Section: Introductionmentioning
confidence: 99%